Principales aspectos del nuevo rol del Contador Público en la aplicación de las NIIF para Pymes en Colombia (2015)
The professional accounting area gets a very important role in the development of daily activities in an organization, yet it is one of the works unless recognized by administrators and managers, since it is seen only as the qualified person for lawful spells decreasing as many potential costs and expenses. In Colombia currently being implemented IFRS concept arising from the 1314 Act of 2009, which makes a real traditional accounting romp; that is why this article seeks to change the assessment where the accounting and financial professional just focus being the person who advises on taxation, to become the professional that guides the company in unifying concepts with the world .